Characterization of thoeniicin 447 produced by Propionibacterium thoenii - Van der Merwe, Iansha (Iansha Rosalia), 1975- (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2002.